Einar Mikkelsen (1880-1971) - Schledermann, Peter (ARCTIC, 1991)
"Einar Mikkelsen, or Mikkel, as he was often called, would have been quite at home in the old Norse society. Exploring new lands and seeking tough challenges in the northern regions of the world was as much in Mikkel's blood as any Norseman could have wished for himself." This profile recounts the remarkable expeditions to Greenland and Alaska, undertaken by Mikkelsen, under the most extreme conditions, and tells of his involvement with Greenland and Greenlanders. Even at the age of 65 he continued his efforts to provide the Greenlanders with some protection between the old and the new worlds. He was very aware of how difficult it would be for the Greenlanders to create a workable amalgamation of the Western and the traditional worlds. He understood as well as anyone that only by living in reasonably small settlements spread out on the land could the people continue to maintain most of the old hunting way of life. He was one of the principal founders of the Danish Arktisk Institut and served on the publications committee of the Arctic Institute of North America throughout the 1950s.